Synthesis and Crystal Structure Analysis of Histone Deacetylase Inhibitor Chidamide - Han, Bo; Peng, Xin-Yan; Gong, Yan-Qing; Zhong, Jia-Liang; Zhang, Qing-Wei (Pharmaceutical Fronts, 2023)
Chidamide is the first oral subtype-selective histone deacetylase inhibitor approved in China for the treatment of relapsed and refractory peripheral T cell lymphoma. Due to the existence of isomers, many articles or patents have mistaken its structure. Herein we explored the synthesis of the key intermediate (E)-4-((3-(pyridin-3-yl)acrylamido)methyl)benzoic acid (A-3) and chidamide, using the condensing agent HBTU, instead of the unstable N,N'-carbonyldiimidazole. The single crystal of chidamide was determined by X-ray diffraction study. The optimized preparation process was easy to operate, and the purity of the final product can be up to 99.76%. Moreover, the structure of chidamide was established to be (E)-N-(2-amino-4-fluorophenyl)-4-((3-(pyridin-3-yl)acrylamido)methyl)benzamide.
Keywords: histone deacetylase; chidamide; synthesis; HBTU; single crystal